1986
DOI: 10.1007/bf00541315
|View full text |Cite
|
Sign up to set email alerts
|

Serum and synovial fluid histidine: a comparison in rheumatoid arthritis and osteoarthritis

Abstract: The serum and synovial fluid (SF) histidine, sulphydryl, and protein concentrations were compared in simultaneous samples from 84 patients with rheumatoid arthritis (RA) and a control group comprising 29 patients with osteoarthritis (OA). The SF levels of histidine were higher than the serum levels in the RA patients but significantly lower than corresponding results in patients with OA (P less than 0.001). The latter had levels of serum and SF histidine which were equivalent and within the normal range. Great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

1995
1995
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…However, the serum concentration of histidine itself is not associated with knee osteoarthritis in the current study. This is consistent with previous reports21 22 in which the concentration of histidine in both serum and synovial fluid were equivalent and within the normal range in knee osteoarthritis patients but significantly lower in rheumatoid arthritis patients. However, Lamers et al 6 suggested that osteoarthritis patients had a lower level of histidine and methylhistidine in urine.…”
Section: Discussionsupporting
confidence: 93%
“…However, the serum concentration of histidine itself is not associated with knee osteoarthritis in the current study. This is consistent with previous reports21 22 in which the concentration of histidine in both serum and synovial fluid were equivalent and within the normal range in knee osteoarthritis patients but significantly lower in rheumatoid arthritis patients. However, Lamers et al 6 suggested that osteoarthritis patients had a lower level of histidine and methylhistidine in urine.…”
Section: Discussionsupporting
confidence: 93%
“…Previous findings have suggested that histidine catabolism is increased in patients with RA, although the reasons for this are unclear [33]. None of the direct products of histidine metabolism were detected in this study, but this should be the topic of a future study because of its apparent importance in RA and it might possibly lead to a better understanding of the pathophysiology of RA.…”
Section: Discussionmentioning
confidence: 60%
“…However, with mean normal and rheumatoid levels of 1.192× l0 -4 and 1.005× l0 -4 mol-dm -3 respectively, little Cu(II) binding capacity is lost. Moreover, rheumatoid synovial fluid histidine levels have been reported to be higher than those of matched sera [23].…”
Section: Discussionmentioning
confidence: 99%